Metagenomic Insights Into the Cycling of Dimethylsulfoniopropionate and Related Molecules in the Eastern China Marginal Seas - Song, Delei; Zhang, Yunhui; Liu, Ji; Zhong, Haohui; Zheng, Yanfen; Zhou, Shun; Yu, Min; Todd, Jonathan D.; Zhang, Xiao-Hua (Frontiers in Microbiology, 2020)
The microbial cycling of dimethylsulfoniopropionate (DMSP) and its gaseous catabolites dimethylsulfide (DMS) and methanethiol (MeSH) are important processes in the global sulfur cycle, marine microbial food webs, signaling pathways, atmospheric chemistry and potentially climate regulation. Many functional genes have been identified and used to study the genetic potential of microbes to produce and catabolise these organosulfur compounds in different marine environments. Here, we sampled seawater, sediment and hydrothermal sediment and polymetallic sulfide in the eastern Chinese marginal seas and analysed their microbial communities for the genetic potential to cycle DMSP, DMS and MeSH using metagenomics. DMSP was abundant in all sediment samples, but was 5- fold less prominent in those from hydrothermal samples. Indeed, Yellow Sea sediment samples had DMSP concentrations 2 orders of magnitude higher than in surface water samples. Bacterial genetic potential to synthesis DMSP (mainly in Rhodobacteraceae bacteria) was far higher than for phytoplankton in all samples, but particularly in the sediment where no algal DMSP synthesis genes were detected. Thus, we propose bacteria as important DMSP producers in these marine sediments. DMSP catabolic pathways mediated by the DMSP lyase DddP (prominent in Pseudomonas and Mesorhizobium bacteria) and DMSP demethylase DmdA enzymes (prominent in Rhodobacteraceae bacteria) and MddA-mediated MeSH S-methylation are very abundant in Bohai Sea and Yellow Sea sediments (BYSS) samples. In contrast, the genetic potential for DMSP degradation was very low in the hydrothermal sediment samples - dddP was the only catabolic gene detected and in only one sample. However, the potential for DMS production from MeSH (mddA) and DMS oxidation (dmoA and ddhA) was relatively abundant. This metagenomics analysis does not provide conclusive evidence for DMSP cycling; however, it does highlight the potential importance of bacteria in the synthesis and catabolism of DMSP and related compounds in diverse sediment environments.